(untitled) (Research, Society and Development, 2022)
Tuberculosis is an infectious disease caused by the bacterium Mycobaterium tuberculosis. Its spread between individuals occurs through direct contact, as infected people eliminate droplets of saliva containing infectious bacilli when talking, coughing and sneezing. However, its transmission can also occur indirectly, through contact with contaminated objects. Although the disease has significantly cheap and effective treatment and diagnosis, it still represents a public health problem in several nations, with considerable morbidity and mortality and higher prevalence in underdeveloped or developing countries. Brazil presents itself as one of the nations that show high rates of tuberculosis, with an approximate value of 60 to 70 thousand cases per year, distributed by national regions. Thus, the present work aimed to carry out a descriptive epidemiological study on tuberculosis in the state of Paraíba, aiming to compare two municipalities in the northeastern state: Campina Grande and João Pessoa. The objective is to present that, within the same state, it is possible to observe different realities with regard to the spread and pattern of infectious diseases. An extraction of data from notifications from the Notifiable Diseases Information System was performed, selecting the following variables: "Sex", "Age Group", "Education", "Ethnicity/Race", "Smoking", "Illicit Drugs", “Diabetes”, “Alcoholism” and “Form of the disease”.